Biocontrol Agents Increase the Specific Rate of Patulin Production by Penicillium expansum but Decrease the Disease and Total Patulin Contamination of Apples - Zheng, Xiangfeng; Yang, Qiya; Zhang, Xiaoyun; Apaliya, Maurice T.; Ianiri, Giuseppe; Zhang, Hongyin; Castoria, Raffaello (Frontiers in Microbiology, 2017)
Abstract Synthetic fungicides are commonly employed for the control of postharvest diseases of fruits. However, due to health concerns about the use of these chemicals, alternative control methods including biocontrol based on antagonistic yeasts are gaining in popularity. In this study, we investigated the effects of two biocontrol yeasts, Rhodotorula mucilaginosa strain 3617 and Rhodotorula kratochvilovae strain LS11, on blue mold and patulin contamination caused by Penicillium expansum strains PY and FS7 in artificially inoculated Fuji apples stored at 20 °C for 9 days. To correlate the development of the P. expansum strains in yeast-treated and untreated apples with patulin production, we quantified their biomass in the infected fruits using a recently published quantitative real time polymerase chain reaction method based on specific primers for patF, a gene from P. expansum that is involved in patulin biosynthesis. Both yeasts significantly reduced the disease incidence caused by the two strains of P. expansum up to 5-7 days of incubation, and lowered their biomass and the progression of symptoms up to 9 days. Interestingly, both yeasts strains increased the rate of patulin production (expressed as ng patulin/μg fungal DNA) by the two pathogenic strains. Nevertheless, both biocontrol agents reduced the total patulin contamination, especially in the case of P. expansum strain FS7, the higher patulin producer of the two tested P. expansum strains. Comparing between the yeast strains, R. kratochvilovae LS11 was more effective than R. mucilaginosa 3617 for the control of P. expansum.